VISPAR: A VISUAL TOOL FOR DESIGNING PARALLEL PROGRAMS - Gorlatch, Sergei; Kehbel, Henry (International Journal of Computing, 2002)
We describe VisPar - a new visual tool intended to support the programmer in the process of designing complex parallel applications. The novel features of the tool are as follows: support of both task and data parallelism and mixture thereof, use of analytical cost models for performance prediction, systematic program design by optimizing transformations, and visualization of the design process. We demonstrate the usage of VisPar on a relevant case study - the practically used Jpeg compression algorithm and report on the current status of the tool implementation.